The Sustainability science of wetland conversion - Roumasset, James (Asian Journal of Agriculture and Development, 2010)
In contrast to traditional resource economics, Sustainability Science accounts for resource interdependencies. Without markets that internalize resource interactions, externalities may result in inefficiencies in the absence of corrective policies. In this paper, the authors construct an ecological-economic model incorporating offshore effects of wetland management. A change in land use affects offshore nutrients, which affect fishery. The authors obtained closed-form expressions for corrective taxation and the shadow price of wetland conversion and provide dynamic numerical simulation for mangrove-shrimp farm management and the impacts on the offshore fishery at Bandon Bay area in Surrathani province, southern Thailand. Results show that converting 1 km2 of shrimp farm into mangrove increases the fishery output and the fish stock in the area by around 3.3 percent, This forgone external benefit from conserving the mangrove should be added to the other costs of converting the mangrove to a shrimp farm for a more complete socila benefit-cost analysis.